Blue Eyes - Daniels, Kelcee L. (Cornfield Review, 2013)
This is my beautiful Siberian Husky, Navi. Don't let those captivating eyes fool you. She is one adventurous and ornery pup, but my husband and I don't know what we would do without her in our lives!